Inhibition of ACAT, overexpression of cholesterol transporter gene, and protection of amyloid β oligomers-induced neuronal cell death by tricyclic pyrone molecules - Pokhrel, Laxman; Maezawa, Izumi; Nguyen, Thi D.T.; Chang, Kyeong-Ok; Jin, Lee-Way; Hua, Duy H. (My University, 2012)
Alzheimer’s disease (AD) is the most common cause of dementia in the elderly. A major effort in AD therapeutic development has targeted Aβ and downstream events. We have taken a rational design approach and synthesized a small library of tricyclic pyrone compounds based on CP2. Their protective action in MC65 cells and the inhibition of acyl‐CoA:cholesterol acyltransferase along with the upregulation of cholesterol transporter gene were investigated. Five most active compounds exhibited potencies in the nanomolar to low micromolar ranges. The multiple effects of the compounds on Aβ and cellular cholesterol pathways could be potential mechanisms underlying the protective effects in vivo.
Inhibition of Acyl-CoA: Cholesterol acyltransferase (ACAT), overexpression of cholesterol transporter gene, and protection of amyloid β (Aβ) oligomers-induced neuronal cell death by tricyclic pyrone molecules
Keywords: Alzheimer’s disease; Aβ; Tricyclic pyrone molecules; Cholesterol transporter gene; Acyl‐CoA:cholesterol acyltransferase